2014
DOI: 10.1088/2041-8205/787/1/l15
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Star Formation in Nearby Legus Galaxies

Abstract: Hierarchical structure in ultraviolet images of 12 late-type LEGUS galaxies is studied by determining the numbers and fluxes of nested regions as a function of size from ∼1 to ∼200 pc, and the number as a function of flux. Two starburst dwarfs, NGC 1705 and NGC 5253, have steeper number-size and flux-size distributions than the others, indicating high fractions of the projected areas filled with star formation. Nine subregions in seven galaxies have similarly steep number-size slopes, even when the whole galax… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 48 publications
6
46
0
Order By: Relevance
“…The same observational signature is also present in the age and positions of the young star clusters in the LMC (Efremov & Elmegreen 1998) and other local galaxies (Grasha et al 2017). Additionally, local star-forming environments in the MW display distributions that are consistent with predictions of hierarchically structured star formation (Bressert et al 2010) that is also observed in extragalactic studies, arising from the molecular cloud hierarchical structure (Elmegreen 2008;Elmegreen et al 2014).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The same observational signature is also present in the age and positions of the young star clusters in the LMC (Efremov & Elmegreen 1998) and other local galaxies (Grasha et al 2017). Additionally, local star-forming environments in the MW display distributions that are consistent with predictions of hierarchically structured star formation (Bressert et al 2010) that is also observed in extragalactic studies, arising from the molecular cloud hierarchical structure (Elmegreen 2008;Elmegreen et al 2014).…”
Section: Discussionsupporting
confidence: 80%
“…Most structures within the hierarchy are themselves gravitationally unbound and the stellar components are expected to inherit their clustered substructure from the molecular clouds from which they are born (Scalo 1985). Recent analyses of 12 local galaxies (Elmegreen et al 2014) found that the clustering of star formation remains scalefree, up to the largest scales observable, for both starburst galaxies and more quiescent starforming galaxies. This result is consistent within the framework where the self-similar structure of the interstellar medium (ISM), regulated by turbulence, is believed to be the primary driver for the hierarchical nature of star formation (Elmegreen & Efremov 1996;Elmegreen et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…D 2 derived in this work is close to those for NGC 628 (D 2 = 1.5; Elmegreen et al 2006), NGC 6503 (D 2 = 1.7; Gouliermis et al 2015), and part of the galaxy sample of Elmegreen et al (2014), but it can deviate more than the measurement uncertainties compared with other ones. Elmegreen et al (2014) found that compared with large spiral galaxies or low surface brightness dwarfs, the starburst dwarfs or HII galaxies have larger projected fractal dimensions if they contain one or two dominant young stellar complexes; thus, the difference in D 2 may reflect different clustering under different conditions. Secondly, older stellar populations have a smaller degree of substructures due to dynamical evolutions (Gieles et al 2008;Bastian et al 2009;Parker et al 2014;Gouliermis et al 2015); this effect may also contributes to the difference in D 2 , since these studies rely on different stellar samples which may be complicated mixtures of populations of various ages.…”
Section: Group Sizessupporting
confidence: 75%
“…On larger scales, a number of galaxies display galaxy-wide hierarchies formed by young stars (e.g. Bastian et al 2007Bastian et al , 2009; Gieles et al 2008;Elmegreen & Elmegreen 2001;Elmegreen et al 2006Elmegreen et al , 2014Gouliermis et al 2010Gouliermis et al , 2015. These studies show that hierarchical stellar structures, significant for a high degree of substructure and an absence of characteristic scales, exhibit self-similar and fractal properties.…”
Section: Introductionmentioning
confidence: 86%